Effect of intermittent or continuous feeding and amino acid concentration on urea‐to‐creatinine ratio in critical illness. Issue 4 (19th September 2021) - Flower, Luke; Haines, Ryan W.; McNelly, Angela; Bear, Danielle E.; Koelfat, Kiran; Damink, Steven Olde; Hart, Nicholas; Montgomery, Hugh; Prowle, John R.; Puthucheary, Zudin
Abstract: Background: We sought to determine whether peaks in essential amino acid (EAA) concentration associated with intermittent feeding may provide anabolic advantages when compared with continuous feeding regimens in critical care. Methods: We performed a secondary analysis of data from a multicenter trial of UK intensive care patients randomly assigned to intermittent or continuous feeding. A linear mixed‐effects model was developed to assess differences in urea‐creatinine ratio (raised values of which can be a marker of muscle wasting) between arms. To investigate metabolic phenotypes, we performed k‐means urea‐to‐creatinine ratio trajectory clustering. Amino acid concentrations were also modeled against urea‐to‐creatinine ratio from day 1 to day 7. The main outcome measure was serum urea‐to‐creatinine ratio (millimole per millimole) from day 0 to the end of the 10‐day study period. Results: Urea‐to‐creatinine ratio trajectory differed between feeding regimens (coefficient −.245; P = .002). Patients receiving intermittent feeding demonstrated a flatter urea‐to‐creatinine ratio trajectory. With k‐means analysis, the cluster with the largest proportion of continuously fed patients demonstrated the steepest rise in urea‐to‐creatinine ratio. Neither protein intake per se nor serum concentrations of EAA concentrations were correlated with urea‐to‐creatinine ratio (coefficient = .088 [ P = .506] and coefficient <.001 [ P = .122], respectively). Conclusion: Intermittent feeding can mitigate the rise in urea‐to‐creatinine ratio otherwise seen in those continuously fed, suggesting that catabolism may have been, to some degree, prevented.